Gut Microbiota, Blood Metabolites, and Spleen Immunity in Broiler Chickens Fed Berry Pomaces and Phenolic-Enriched Extractives - Das, Quail; Islam, Md. Rashedul; Lepp, Dion; Tang, Joshua; Yin, Xianhua; Mats, Lili; Liu, Huaizhi; Ross, Kelly; Kennes, Yan Martel; Yacini, Hassina; Warriner, Keith; Marcone, Massimo F.; et al. (Frontiers in Veterinary Science, 2020)
This study evaluated the performance, gut microbiota and blood metabolites in broiler chickens fed cranberry and blueberry products for 30 days. A total of 2800 male day-old broiler Cobb 500 chicks were randomly distributed between 10 diets: control basal diet; basal diet with bacitracin (BACI), 4 basal diets with 1% and 2% of cranberry (CP1, CP2) and blueberry (BP1, BP2) pomaces; 4 basal diets supplemented with ethanolic extracts of cranberry (COH150, COH300) or blueberry (BOH150, BOH300) pomaces. All groups were composed of seven replicates and 40 birds were included in each replicate. Cecal and cloacal samples were collected for bacterial counts and 16S rRNA gene sequencing. Blood samples and spleen were analyzed for blood metabolites and gene-expressions, respectively. The supplementation of COH300 and BOH300 significantly increased the BW during the starting and growing phases, respectively; while COH150 improved (P < 0.05) the overall cumulated feed efficiency compared to control. The lowest prevalence (P = 0.01) of necrotic enteritis was observed with CP1 and BP1 compared to BACI and CON. Cranberry pomace significantly increased quinic acid level in blood plasma compared to other treatments. At days 21 and 28 of age, the lowest (P < 0.05) levels of triglyceride and alanine aminotransferase were observed in cranberry pomace and blueberry products-fed birds, respectively suggesting that berry feeding influenced the lipid metabolism and serum enzyme levels. The highest relative abundance of Lactobacillaceae was found in ceca of birds-fed CP2 (P < 0.05). In cloaca, BOH300 significantly (P < 0.005) increased the abundances of Acidobacteria, and Lactobacillaceae. Actinobacteria showed a significant (P < 0.05) negative correlation with feed intake and feed efficiency in COH300 treated birds, whereas Proteobacteria positively correlated with the BW but negatively correlated with FI and FE; during the growing phase. In the spleen, cranberry products did not induce the release of any pro-inflammatory cytokines, but upregulated the expression of several genes (IL4, IL5, CSF2, and HMBS) involved in adaptive immune responses in broilers. This study demonstrated that feed supplementation with berry products could promote the intestinal health by modulating the dynamics of gut microbiota while influencing the metabolism in broilers.